Prevalence of dry eye disease among operating room nurses in tertiary care hospital: Cross-sectional survey - Natwarlal Patidar; Talagatoti David Ratna Paul; Ravi Gaur; Shoma Mukharjee; Nitika Thakur; R Sreeraja Kumar (The Indian Anaesthetists' Forum, 2025)
Background: The escalating global incidence of dry eye disease (DED) necessitates heightened attention from nursing professionals, given its detrimental impact on patient well-being. Despite extensive research on DED, a notable dearth of literature exists regarding its occurrence among Operation Theatre (OT) nurses in India. Consequently, this study seeks to evaluate the prevalence, severity, and contributory factors of DED among OT nurses in Indian healthcare. The result of the present research will provide the guidance on how to maintain the eye sight health of nursing officers who are spending more time in operating theatre. Aims and Objectives: The primary objective of the study was to analyse prevalence Dry Eye Disease among Operating Room Nursing Officers based on Ocular Surface Disease Index (OSDI) questionnaire. The secondary objective was to find association of risk factors and dry eye disease among Operating Room Nursing Officers. Methods and Material: The study was conducted at AIIMS Jodhpur, a tertiary care teaching hospital in western Rajasthan, India using cross-sectional study design. The population under study were 162 nurses from all operation theatres of the hospital. The sample size was determined to be 115 operating room nurses. The study was conducted from May 2023 to August 2023. Data collected using Socio-demographic sheet and Ocular Surface Disease Index (OSDI) questionnaire. Appropriate Descriptive and inferential statistics were used for data analysis. Results: In this study, the mean age of the participants was 28.45 years and among the nursing officers, 75.65% were male. Significant DED was detected in 43.5% (50/115) of nursing officers working in operating room. Out of this 22.9% (26/50) had mild DED, 12.2% (14/50) had moderate and 08.4% (10/50) had sever DED. The prevalence of dry eye disease is more in females (48.1% Female; 40.7% Male) and in nursing officers with age below 30 years (44.8%). There is significant difference is identified between contact lens usage and presence of DED (P=0.03). Conclusions: According to the results, the prevalence of dry eye disease is not much sever in operating room nursing officers but participants do have mild and moderate symptoms of related to ocular and vision related functions. Prolong working hours in indoor environment, exposure under operating room lights, focused vision on surgical site, High humidity and higher particulate matter may be contributing factors put nursing officer at risk to get dry eye disease in operating room setting.